Identity Construction of Fans: Virtual Community Through Chat Room LINE (Case Study EXO-L Bandung Community) - Kumala Hayati; Anindita Lintangdesi Afriani (Journal of Communication and Public Relations, 2022)
For fans outside of South Korea, the existence of social media can open the possibility to follow all their idol activities and express their identity as fans freely because not all community can accept them. LINE is a medium of information exchange that forms a fan culture as a form of identity consumption of the fans. This research uses a qualitative method with Creswell's constructivism paradigm discussing identity construction among members of Bandung EXO - L community. LINE chat group is a discussion forum to learn how to support idols by conducting virtual fangirling activities that become the lifestyle of community members. Thus, the community environment shapes both verbal and non-verbal communication between community members. This has an impact on the emergence of loyal and active feelings possessed by community members. This loyalty is interpreted as obligations for fan identity because consuming EXO related stuffs is not only based on the work produced, but as an absolute identity.